-3 (1,2x-2)-(4-4,6x)+6 (0,2x-1) при x= 15/12 у вырожение

liz93 liz93    1   10.04.2020 11:29    0

Ответы
ВДРПДАОЦПУЦ ВДРПДАОЦПУЦ  10.04.2020 11:30

- 3 (1,2х - 2) - (4 - 4,6х) + 6 (0,2х - 1) = - 3 * 1.2x - 3 * (- 2) - 4 + 4.6x + 6 * 0.2x - 1 * 6 = - 3.6x + 6 - 4 + 4.6x + 1.2x - 6 = x (- 3.6 + 4.6 + 1.2) - 4 = 2.2x - 4.

х = - 15/22.

2.2x - 4 = 2.2 * (- 15/22) - 4 = - 22/10 * 15/22 - 4 = - 15/10 - 4 = - 1.5 - 4 = - 5.5.

ответ: 2.2x - 4 = - 5,5 при х = - 15/22.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика